(untitled) (Research, Society and Development, 2020)
The present study analyzed the scientific literature in search of information that can contribute to the knowledge about the analysis of indexes that are considered factors of predisposition to heart problems after non-surgical periodontal treatment, more specifically lipid profile, glycated hemoglobin ( HbA1c) and C-reactive protein (PCR). As the present study is a literature review, for its production, the databases were consulted: Biblioteca Virtual em Saúde (BVS), Publicações Médicas (PubMed), Medline e biblioteca virtual Scientific Eletronic Library online (SCIELO). To carry out this research, we used the Descritores em Ciência da Saúde (DECS): periodontal diseases, dental scaling and cardiovascular diseases. The review demonstrated the fact that increases in CRP concentration are predictive of cardiovascular diseases (CVDs), and can be directly associated with the progress of atheromatous plaques formed in the carotid arteries. It also showed that untreated periodontitis is associated with possible alterations in lipid metabolism. In addition, lipid alterations in this context would be caused by infection that induces atherogenic changes in lipoprotein profiles. It was also seen that periodontal treatment performed correctly, works as a way to improve the clinical parameters of periodontal disease, as well as to favor the metabolic control of glucose in diabetic individuals, since periodontal disease can mean prognostic value for these cases. It is concluded that with this review there is evidence that non-surgical periodontal treatment can influence the decrease in levels of CRP, HbA1c and hyperlipidemia in patients with CVDs